Chasing the high - Keegan, Kyle (Oxford University Press, 2008)
Now in recovery, Keegan tells his remarkable story in Chasing the High. Starting with the early days of alcohol and drug use, Keegan charts his decline into crime and homelessness as his need for heroin surpassed all thoughts of family and friends, of right and wrong. He then goes on to use these experiences to offer guidance and practical advice to other young people who may be struggling with substance abuse. In straightforward, easy-to-understand language and along with the psychiatric expertise of Howard Moss, MD, Keegan discusses what is known about the neurobiology of addiction in young people, how to seek treatment, and how to get the most out of professional help. He also covers such topics as therapies which are used to combat addiction, how to talk to families and friends about substance abuse, and how to navigate risky situations. Both an absorbing memoir and a useful resource for young people